Proceedings of the 13th ACM Great Lakes Symposium on VLSI - GLSVLSI '03 2003
DOI: 10.1145/764825.764831
|View full text |Cite
|
Sign up to set email alerts
|

Cooling of integrated circuits using droplet-based microfluidics

Abstract: Decreasing feature sizes and increasing package densities are making thermal issues extremely important in IC design. Uneven thermal maps and hot spots in ICs cause physical stress and performance degradation. Many MEMS and microfluidics-based solutions were proposed in the past. We present a cooling method based on high-speed electrowetting manipulation of discrete submicroliter droplets under voltage control with volume flow rates in excess of 10 mL/min. We also propose a flow-rate feedback control where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…EWOD can be used for transporting electrically conductive liquid metals and alloys; these fluids typically demonstrate orders of magnitude higher thermal conductivities than non-metallic liquids such as water or oils [7]. Galinstan, 1 an inexpensive eutectic gallium/indium/tin alloy commonly used in modern medical thermometers, has a thermal conductivity 65 times higher than water's.…”
Section: Introductionmentioning
confidence: 99%
“…EWOD can be used for transporting electrically conductive liquid metals and alloys; these fluids typically demonstrate orders of magnitude higher thermal conductivities than non-metallic liquids such as water or oils [7]. Galinstan, 1 an inexpensive eutectic gallium/indium/tin alloy commonly used in modern medical thermometers, has a thermal conductivity 65 times higher than water's.…”
Section: Introductionmentioning
confidence: 99%
“…Fast and efficient cooling of hot spots has remained a major challenge while designing the latest cooling strategies. In this respect, Digital microfluidics (DMF) [4,5] technology may offer a better alternative for chip cooling as it can efficiently handle discrete droplets of small volume, and provide enhanced process rate due to the high surface to volume ratio [6]. A recent study also shows an enhancement in the cooling efficiency by pulsating DC voltage induced oscillating droplets [7].…”
Section: Introductionmentioning
confidence: 99%
“…The key application areas driving this interest include lab-on-chip systems, electrowetting-based optics and liquid displays. There has been recent interest in using electrowetting for heat transfer applications [3][4][5]; as an illustration, electrowetting-based microelectronics thermal management (package level as well as site-specific hot spot thermal management) has been the focus of some recent research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported experimental measurements of the heat transfer performance of electrowetting-based droplet systems. Pamula and Chakrabarty [3] suggested the use of an electrowetting-based digital microfluidic system for cooling hot spots in integrated circuits. They also proposed a dynamic cooling system utilizing thermocapillarity and electrowetting; hot spots on the chip would attract higher flow rates due to thermocapillarity, and this hot fluid would be returned to the reservoir using electrowetting-based pumping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation